2012
DOI: 10.1155/2012/190624
|View full text |Cite
|
Sign up to set email alerts
|

Subcapsular Orchiectomy in the Primary Therapy of Patients with Bone Metastasis in Advanced Prostate Cancer: An Anachronistic Intervention?

Abstract: Background. The therapeutic impact of palliative androgen deprivation in metastatic prostate cancer is indisputable. Bilateral orchiectomy represents the traditional method of AD but was reduced during the last years in favor for treatment with LHRH analogues. Due to limited economic resources of the health care system, the economically priced definite surgical castration might experience a renaissance. Methods. In this single-center retrospective study, 83 consecutive patients with osseous metastasized prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
14
3
Order By: Relevance
“…Orchiectomy in other species can be performed painlessly after injecting the testes or spermatic cords with local anesthetic. Men can be castrated using local anesthesia, often without sedation (1)(2)(3)(4). Stallions also are often castrated while they are standing by using only sedation, local anesthesia, and a lip twitch for restraint (5).…”
Section: Introductionmentioning
confidence: 99%
“…Orchiectomy in other species can be performed painlessly after injecting the testes or spermatic cords with local anesthetic. Men can be castrated using local anesthesia, often without sedation (1)(2)(3)(4). Stallions also are often castrated while they are standing by using only sedation, local anesthesia, and a lip twitch for restraint (5).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical and medical castration is considered to increase overall survival rate [11]. Rud O et al stated that advantages of orchidectomy are rapidly effective in lowering testosterone level which is achieved between 3 to 12 hours after surgery and is related with good compliance [12]. Goldenberg et al added that this form of therapy improves quality of life when the patient is androgen hormone receptor sensitive by giving them life with therapy free interval [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients in our study were asked during follow-up whether they experienced this distress, and we found that 19% of patients who underwent the subcapsular technique and 60% of those who underwent the total technique were not psychologically satisfied with the procedure. In other studies comparing these techniques, psychological problems are mentioned but the patients were not asked to rate their satisfaction (1,8).…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for 28% of all cancers in males. Although the introduction of the prostate-specific antigen (PSA) test in the 1960s has facilitated the diagnosis of prostate cancer, 5-10% of these patients are diagnosed with distant metastasis (1). Diethylstilbestrol treatment was first prescribed after it was discovered that prostate cancer is an androgen-dependent condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation